Answer:
[tex]f^{-1}(x)=log_3(x+1)[/tex]
Step-by-step explanation:
Function f(x) is defined as: [tex]f(x)=3^x-1[/tex]
In order to find its inverse ([tex]f^{-1} (x)[/tex], we need in the first step, to replace f(x) by the variable "y": [tex]f(x)=3^x-1\\y=3^x-1[/tex]
In the next step, we solve for "x" as a function of "y". Notice that we need to use the logarithm base 3 to bring the exponent "x" down:
[tex]y=3^x-1\\y+1=3^x\\log_3(y+1)=log_3(3^x)=x\\x=log_3(y+1)[/tex]
Next, we replace y with "x", and x with [tex]f^{-1}(x)[/tex]
[tex]x=log_3(y+1)\\f^{-1}(x)=log_3(x+1)[/tex]